Pengaruh Kompensasi Manajemen, Pertumbuhan Penjualan, Umur Perusahaan, Kepemilikan Institusional dan Kepemilikan Manajerial Terhadap Penghindaran Pajak - Dwi Krisna; Clara Susilawati (Journal of Management and Bussines (JOMB), 2023)
In all manufacturing companies registered on the Indonesia Stock Exchange, this study tries to ascertain the impact of management salary, sales growth, company age, institutional ownership, and managerial ownership on tax avoidance. The Purposive Sampling approach was utilized to determine the research sample, and it led to the final study sample of 69 companies. The findings of this study demonstrate that institutional ownership, managerial ownership, and management compensation all have a favorable impact on tax evasion. In the meantime, tax avoidance is negatively impacted by both business age and sales growth. In conclusion, tax evasion is positively impacted by management salary, sales growth, firm age, institutional ownership, and managerial ownership. Keywords: Management Compensation, Sales Growth, Company Age, Tax Avoidance